Will the singing have to stop - booze or culture? radio programme in NSW Folk Federation collection - Bowden, Tim, 1937-; Stanton, Bob; Egan, Ted, 1932-; Blanatji, David, approximately 1930-; Randall, Bob (Robert James), 1934-2015.; Watkins, Cherie; Laiwonga, Tjoli; New South Wales Folk Federation; Australian Broadcasting Commission; Macquarie University. Centre for Advancement of Teaching (1976)
Folkloric recording. Documentary examining the impact of European life on Aboriginal culture.Documentary surveying the survival of traditional music in areas including the Torres Strait Islands, Bathurst Island, and the Bamyili and Yuendumu Indigenous Australian communities in Central Australia.
Aboriginal and Torres Strait Islander people are advised that this recording may contain names and voices of deceased persons.
Dubbing of a documentary radio programme broadcast by ABC FM Stereo on May 25, 1976. Programme is produced by Tim Bowden, recorded by Bob Stanton, and features Ted Egan, David Blanatji, Bobby Randall, Cherie Watkins, Tjoli Laiwonga.
Recording dubbed on May 25, 1976 at Macquarie University, Sydney, N.S.W.
Digital master available
Keywords: Aboriginal Australians -- Social life and customs; Aboriginal Australians -- Songs and music; Torres Strait Islanders -- Social life and customs; Torres Strait Islanders -- Songs and music; Radio programs -- Australia; Australia -- Ethnic relations